PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN KARO - Benni Purba; Menanti Sembiring (JURNAL REGIONOMIC, 2020)
Human resoucers play a very important role in on organization because human resourcesare the main generator of all activities of organization. The survival of the organization is largely determined by human resources who have good work discipline. This study aims to determine the effect of work discipline on employee performance at the Karo District Transportation Department. The sampling technique in this study using a total sample where the entire population in this study was used as a sample, namely a number of 51 people. Primary data were collected through a questionnaire. The analytical method used is simple linear regression analysis. To test the proposed hypothesis, the t test and the coefficient of determination test. The results showed that the work discipline variable had a significant effect on the performance of the employees of the Karo Regency Transportation Department. The results of simple linear regression analysis obtained regression equation Y = 11,261 + 0,803X + e. The coefficient of determination obtained is 0.496 or 49.60%, the performance of the Karo District Transportation Department employees is influenced by work discipline.